2005
DOI: 10.1128/iai.73.12.8179-8187.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ectophosphorylation of CD36 Regulates Cytoadherence of Plasmodium falciparum to Microvascular Endothelium under Flow Conditions

Abstract: The adhesion of Plasmodium falciparum-infected erythrocytes (IRBCs) to human dermal microvascular endothelial cells (HDMECs) under flow conditions is regulated by a Src family kinase-and alkaline phosphatase (AP)-dependent mechanism. In this study, we showed that the target of the phosphatase activity is the ectodomain of CD36 at threonine-92 (Thr 92 ). Mouse fibroblasts (NIH 3T3 cells) transfected with wild-type CD36 or a mutant protein in which Thr 92 was substituted by Ala supported the rolling and adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 32 publications
(30 reference statements)
2
61
0
Order By: Relevance
“…CD36 acts in cooperation with other host receptors that tether and capture pRBCs from blood flow (14,54). Adhesion of pRBCs to CD36 on endothelial cells has been shown to induce postadhesion signaling events that further strengthen binding by causing CD36 receptor clustering and cytoskeletal rearrangement (18,19). Here, we used concentrations of recombinant CD36 that have previously been shown to support static adhesion of the same parasite clones (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD36 acts in cooperation with other host receptors that tether and capture pRBCs from blood flow (14,54). Adhesion of pRBCs to CD36 on endothelial cells has been shown to induce postadhesion signaling events that further strengthen binding by causing CD36 receptor clustering and cytoskeletal rearrangement (18,19). Here, we used concentrations of recombinant CD36 that have previously been shown to support static adhesion of the same parasite clones (31).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the changes in membrane stiffness help stabilize the rolling velocities of pRBCs by increasing the energy needed to peel the cell membrane away from the substrate. If true, then the development of a stiffer membrane and stabilizing of rolling velocity under microvascular shear stresses represent adaptations that increase the tendency of pRBCs to slow on endothelial cells, followed by postadhesive CD36 signaling events that lead to stable binding (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…& McGregor, 1995) has also been implicated in binding apoptotic cells (Navazo, Daviet, Savill, Ren, Leung, & McGregor, 1996) and modified LDL (Puente Navazo, Daviet, Ninio, & McGregor, 1996), but because antibody binding to this domain disrupts all CD36 functions, it may relate more to conformational change of the receptor than actual binding site for these ligands. An interesting property of CD36 is the ectophosphorylation of threonine 92 which has been shown to impact binding of certain ligands (Asch, et al, 1993,Hatmi, Gavaret, Elalamy, Vargaftig, & Jacquemin, 1996,Ho, et al, 2005. The intracellular domains of CD36 are located on very short cytoplasmic tails: the N-terminal tail is probably the result of an uncleaved signal peptide.…”
Section: Cd36 Structure and Expressionmentioning
confidence: 99%
“…Modulation of the binding of platelets to collagen and thrombospondin-1, and the binding of Plasmodium falciparum infected erythrocytes to microvascular endothelium has been shown to be regulated by phosphorylation/dephosphorylation of the ectodomain of CD36, specifically, threonine 92 (Asch, et al 1993,Ho, et al, 2005. Asch et al found that resting platelets constitutively express phosphorylated CD36, and have greater affinity for collagen compared to TSP-1.…”
Section: Cd36 Ligands and Functionsmentioning
confidence: 99%